Analisis Niat Wisatawan untuk Berkunjung ke Kawasan Kuta Mandalika Lombok - Tarandhika Tantra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Tourism is the sector that has the most potential to contribute greatly to GDP. The competitiveness of Indonesia's tourism sector is lower than the kawasa countries of Southeast Asia. The Government of Indonesia developed the National Priority Tourism Area with the 10 New Bali program in an effort to be competitive and superior. Kuta Mandalika Lombok Area of West Nusa Tenggara is one of the 10 priority areas. This research was conducted to find out the factors that make tourists to visit the Kuta Mandalika Lombok area including destination image, motivation, Word of Mouth and knowledge. Knowledge is believed to moderate the image of the destination. The survey was conducted to 310 respondents who had visited the Kuta Mandalika Lombok Area and conducted an analysis using the SmartPLS application. The findings of this study show that the image of destination, motivation, and Word of Mouth has a positive influence on the intention of visiting kuta mandalika lombok area. Knowledge is proven to have no moderating effect on the relationship of destination imagery and visiting intentions. The local government should develop the image of Kuta Mandalika Lombok area as a world-class priority tourist area in order to attract tourists to visit